Employee Performance Scale: Using (CFA) On Jumhouria Bank In Libya - Mohammad Nashief S.; Esmael M. A. Tabouli; Nasser Habtoor (International Journal of Science and Research, 2024)
The present study seeks to develop a conceptual framework for measuring employee performance in banking institutions by adopting four appropriate dimensions of measurement: Efficiency of the work, Planning the Work, creativity and innovation and Making Efforts. To achieve this goal, we used a confirmatory factor analysis (CFA) through AMOS software. Based on the results, it was found that this model is a valid and reliable model that can be used for measuring employee performance in banking institutions in Libya.